2013
DOI: 10.5603/cj.2013.0069
|View full text |Cite
|
Sign up to set email alerts
|

Tissue coverage of paclitaxel and sirolimus eluting stents in long term follow-up: Optical coherence tomography study

Abstract: Background: Implantation of drug eluting stents (DES) has become a standard treatment of patients undergoing percutaneous coronary intervention (PCI (Cardiol J 2013; 20, 3: 247-253)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Kubo et al ( 55 ) reported that intimal stent coverage was significantly delayed in patients with UAP. Kochman et al ( 56 ) used OCT to follow up the DESs and bare metal stents (BMSs) of diabetic patients for 2 years and observed that the intima remained uncovered 2 years after the DES was implanted. Furthermore, the intimal coverage of the stent is unrelated to whether the patient has diabetes.…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 99%
“…Kubo et al ( 55 ) reported that intimal stent coverage was significantly delayed in patients with UAP. Kochman et al ( 56 ) used OCT to follow up the DESs and bare metal stents (BMSs) of diabetic patients for 2 years and observed that the intima remained uncovered 2 years after the DES was implanted. Furthermore, the intimal coverage of the stent is unrelated to whether the patient has diabetes.…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 99%